Pre-task music improves swimming performance - Smirmaul, B. P.; dos Sant, R. V.; da Silva Neto, L. V. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to investigate the effects of pre-task music on swimming performance and other psychological variables.